2005
DOI: 10.2113/gscanmin.43.5.1511
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Chemistry of the "Nickelalumite"-Group Minerals

Abstract: The crystal structure of "nickelalumite", ideally NiAl 4 (SO 4 )(OH) 12 (H 2 O) 3 , from the Kara-Tangi uranium deposit, Batken region, Kyrgyzstan, monoclinic, a 10.2567 (5) . Intercalated between the M-Al-OH sheets are layers of (SO 4 ) tetrahedra and (H 2 O) groups. All H atoms of (OH) and (H 2 O) groups were located, and details of hydrogen bonding are discussed. The structure of "nickelalumite" is similar to those of alvanite, ZnAl 4 (VO 3 ) 2 (OH) 12 (Traduit par la Rédaction) Mots-clés: "nickelalumite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(93 citation statements)
references
References 12 publications
4
89
0
Order By: Relevance
“…An LDH comprises two 6 ] 0.75 þ . The structure of the metal hydroxide layer was modeled in this manner using the atomic position coordinates extracted from the published structure of nickelalumite [11] (space group P2 1 /n, cell parameters: a¼ 10.305(3) Å, b¼8.911 (2) Å, c ¼17.141 (2) Å, β¼95.68 (2)1). This provided the partial structure model for the refinement.…”
Section: Structure Of the [Zn-al4-nitrate]ldhmentioning
confidence: 99%
See 2 more Smart Citations
“…An LDH comprises two 6 ] 0.75 þ . The structure of the metal hydroxide layer was modeled in this manner using the atomic position coordinates extracted from the published structure of nickelalumite [11] (space group P2 1 /n, cell parameters: a¼ 10.305(3) Å, b¼8.911 (2) Å, c ¼17.141 (2) Å, β¼95.68 (2)1). This provided the partial structure model for the refinement.…”
Section: Structure Of the [Zn-al4-nitrate]ldhmentioning
confidence: 99%
“…Given that the nickelalumite structure has a natural affinity for anions of tetrahedral molecular symmetry [11], the [Zn-Al4-nitrate] LDH is a candidate material for green chemistry applications for efficient sorption of CrO 4 2 À ions from waste water. UV-vis spectra of the chromate intercalated LDH exhibits bands corresponding to that of free chromate indicating intercalation of chromate has occurred (SI.…”
Section: Chromate Uptake Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work (Karpenko 2010) showed that the compositions of these crusts are very complicated. They consist of vanadates and sulfates of the chalсoalumite group (Hawthorne and Cooper 2013): alvanite (Pertlik and Dunn 1990), ankinovichite (Karpenko et al 2004a), nickelalumite (Karpenko et al 2004b;Uvarova et al 2005), kyrgyzstanite , volborthite, V-bearing phosphates, Cr-V-bearing members of the alunite subgroup, members of the pascoite family, and vanadium-bronze oxides including metahewettite. Metahewettite was collected from the old exploration trench at Hodzha-Rushnai-Mazar, 2 km east of the village of Valakish (40º10'15"N 72º 06'33"E).…”
Section: Occurrencementioning
confidence: 99%
“…Because silicate phases are a significant class of minerals observed for natural actinides [1][2][3][4][5][6][7][8], as exemplified by thorite (ThSiO 4 ) [1] and coffinite (USiO 4 ) [3], we are interested in developing synthetic routes from melts that can be used to extend this chemistry to the man-made heavier actinides, Np and Pu. Knowledge in this area is critical to furthering our predictive capabilities regarding the fate and transport of transuranic contaminants in the geosphere [9,10].…”
Section: Introductionmentioning
confidence: 99%